Peningkatan Penguasaan Konsep Usaha Dan Energi Menggunakan Model Flipped Classroom Berbantuan Video Youtube - Lulang, Irma Yani; Latununuwe, Altje; Malawau, Seska; Sabandar, Vederico Pitsalitz; Esomar, Ketarina (Pattimura University, 2023)
Research has been successfully carried out using the flipped classroom model assisted by YouTube videos on the concepts of work and energy. This study aims to determine the increasing mastery of the concept. The research sample was class X MIA6 SMA Negeri 11 Ambon, even semester of the 2021/2022 academic year, which consisted of 32 students. The sampling technique uses purposive sampling. Increased mastery of students' concepts in the high category 96.875% of students and 3.125% of students in the medium category. The average increase in N Gain is 0.80 or in the high category.